2007
DOI: 10.1088/0952-4746/27/1/001
|View full text |Cite
|
Sign up to set email alerts
|

Polonium-210 as a poison

Abstract: The death of Alexander Litvinenko on 23 November 2006 has brought into focus scientific judgements concerning the radiotoxicity of polonium-210 ((210)Po). This paper does not consider the specific radiological circumstances surrounding the tragic death of Mr Litvinenko; rather, it provides an evaluation of published human and animal data and models developed for the estimation of alpha radiation doses from (210)Po and the induction of potentially fatal damage to different organs and tissues. Although uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
6

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 51 publications
1
101
0
6
Order By: Relevance
“…Absorption of Po-210 is reported to possibly have reached 10 % (f 1 = 0.1); however, the authors indicated that the estimate was largely conjectural and may have been considerably overestimated. Higher values for f 1 have been reported when Po-210 is ingested in foods (Harrison et al 2007).…”
Section: Naturally Occurring Po-210 In Human Tissuementioning
confidence: 84%
See 2 more Smart Citations
“…Absorption of Po-210 is reported to possibly have reached 10 % (f 1 = 0.1); however, the authors indicated that the estimate was largely conjectural and may have been considerably overestimated. Higher values for f 1 have been reported when Po-210 is ingested in foods (Harrison et al 2007).…”
Section: Naturally Occurring Po-210 In Human Tissuementioning
confidence: 84%
“…Target cells may therefore include vascular endothelial cells, mesenchymal fibroblast and other cell types (Harrison et al 2007). Animal data revealed an association between ingested Po-210 and intestinal tissue.…”
Section: Naturally Occurring Po-210 In Human Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…210 Po, which has gained considerable attention after the intoxication of Alexander Litvinenko [105], is a naturally occurring radioisotope (T ½ = 138.4 d) of the U radioactive series. 210 Po was estimated to contribute to 60 % of the average world individual effective dose from ingestion of radionuclides from the U and Th series [106].…”
Section: Intestinal Biotransformarion Of Other Metal(loid)s: Ge CD mentioning
confidence: 99%
“…The events of November 2006, however, stimulated and reinvigorated worldwide interest in this relatively obscure element, and those events prompted the authoring of many new articles in the literature about its toxicity and the public health response to this event [16][17][18][19][20][21][22][23][24]. Articles concerning the "biological behavior" of this element have expanded our knowledge about its potential use as a poison.…”
Section: Treating Internal Contaminationmentioning
confidence: 99%